Factors Affecting Performance of International Microfranchises : Case of HealthStore Foundation - Timonen-Nissi, Inari (fi=Turun yliopisto|en=University of Turku|, 2017)
Many people in the world suffer from debilitating poverty and this presents an economic, social, political, and a moral problem. The intent of microfranchising is to alleviate poverty and to provide services to the poor through the replication of business systems at the grassroots micro level. The purpose of this study is to examine microfranchise performance. This study answers the following sub questions concerning the different factors affecting microfranchise performance: • How have the key advantages of the traditional franchise model affected microfranchise performance? • How has the bottom-of-the-pyramid (BOP) institutional environment affected microfranchise performance? • How has a microfranchise been able to adapt the traditional franchise model to mitigate BOP institutional challenges? In this study, case study is chosen to be the research method. The research data consists of an interview conducted with a healthcare microfranchise that has been active in Eastern Africa. To complement this data, some secondary data provided by the case company was also used. The framework by Kistruck et al. (2011) that describes the relationship between franchise performance drivers is complemented with the results of the study in terms of what institutional challenges microfranchises face and how the franchise model has been adapted to improve microfranchise performance. The main institutional challenges to realising the key advantages of the franchise model are the inability of the franchisor to charge royalties, grant dependency, perverse incentives of franchisees and inefficient enforcement, as well as cultural difference across BOP markets. As a social franchise, the case company could not add to the financial burden of its franchisees or raise investor capital. The social franchise model has allowed for the franchise to deliver a quality end-consumer service, however, the model has put restraints on growth. For this reason a new commercial franchise model was set up to address these challenges. The commercial franchise model will allow for the microfranchise to grow sustainably, whilst also delivering a quality service and the desired results. To conclude, the BOP environment has presented challenges to microfranchise performance; however by adapting the franchise model microfranchise performance could be improved.